Experimental investigation of cementitious materials using the prism technique - Messaoudi, Rahma; Bouzerira, Cherif; Grimes, Morad; Oucief, Hocine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Numerous studies have shown that the non-destructive testing has proved the exceptional role in supervising the quality of concrete. Today, they represent an alternative that contributes to the resolution of materials diagnostic problems without altering them. This work presents an experimental study using a pulse-echo method that has the advantage of generating two types of wave (compressional and shear) by a mode conversion using just one transducer. The samples were made in a prismatic form.
Keywords: prism technique; cementitious material; compressional wave; shear wave; reflection coefficient; technika pryzmatyczna; materiał cementowy; ściskanie; fala uderzeniowa; współczynnik odbicia